PENGARUH MULTIMEDIA BERBASIS PROGRAM ADOBE FLASH TERHADAP HASIL BELAJAR IPS DI SEKOLAH DASAR - Nurikhlas, Aditya; Marli, Suhardi; Rosnita, Rosnita (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research was to know the impact of multimedia based on adobe flash program toward the result of learning social sciences student fourth grade Elementary School in Pontianak. The experimental reseach method was used in this research. The form of the experimental research used was quasy experimental design. Population in this research is all students fourth grade which consisted of 45. Sample in this research weer students fourth grade which consisted of 23. Instrument gatherer data of student learning the test results obtained from pre-test and post-test. The result of data analysis showed that mean score of student?s post-test was 76,96. Based on t-test analysis, thitung of (5,71) and ttabel (2,0178). Which means, thitung (5,71) > ttabel (2,0178), thus then Ha accepted. The result of effect size was 1,23 which mean high criteria on ES>0,8. So, it can be concluded there was a significant effect of using multimedia based on adobe flash program to the students learning outcomes on fourth grade Elementary School. Keywords: Multimedia Based on Adobe Flash Program, Study Result, Social Science